PENGARUH PENGGUNAAN E-MODUL BERBASIS FLIP PDF PROFESSIONAL TERHADAP MINAT BELAJAR MATEMATIKA SISWA SMP NEGERI 3 SUNGGUMINASA - Septiani, Hasniar Arun; Muhammad Nawir; Nurindah (Jurnal Riset Guru Indonesia, 2023)
The main problem in this study is whether there is an effect of using Flip PDF Professional-based E-module on students' interest in learning mathematics at SMP Negeri 3 Sungguminasa. This study aims to determine the effect of using an E-module based on Flip PDF Professional on students' interest in learning mathematics at SMP Negeri 3 Sungguminasa. This type of research is quantitative with the Pre-Experimental method with a One-shot case study, which uses treatment and measurement of a class with a quantitative approach. The sample in this study amounted to 78 students. The results of this study indicate that there is an influence on student learning interest after the application of the Flip PDF Professional-based E-module. This can be seen from the results of the Pearson product-moment correlation coefficient test using SPSS 26, it is found that the sig. > 0.005, namely 0.830 > 0.005. Based on the description above, it can be concluded that there is an effect of using Flip PDF Professional-based E-module on students' learning interests.